Comparing the Effectiveness of Well-Being Therapy and Positive Therapy on Affective Capital in Adolescents Residing in Foster Care Centers - Shavaran , Raana; Atashpour , Seyed Hamid; Farhadi, Hadi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to compare the effectiveness of well-being therapy and positive therapy on affective capital in adolescents aged 12 to 18 years residing in foster care centers in Isfahan Province. Methods and Materials: The research employed a quasi-experimental design using a pretest-posttest format with a control group and a three-month follow-up. A total of 45 adolescent girls aged 12 to 18 years were randomly selected and assigned to two experimental groups and one control group (15 participants per group). The experimental groups underwent eight sessions of well-being therapy and positive therapy, respectively, while the control group received no intervention. All three groups were assessed using affective capital questionnaires before the intervention, immediately after, and three months post-intervention. Findings: The results indicated that the mean affective capital significantly increased in both the well-being therapy and positive therapy groups during the post-test and follow-up phases compared to the pretest phase. Conclusion: Based on the findings, it was concluded that well-being therapy and positive therapy are effective in enhancing the affective capital of adolescents residing in foster care centers, with a significant difference observed between the two interventions.